NYERI DAN KEMAMPUAN AKTIVITAS PADA PASIEN KANKER KOLOREKTAL MENJALANI KEMOTERAPI - Khoirunnisa’ Munawaroh, Untung Sujiant Mardiyono (Adi Husada Nursing Journal, 2017)
Nyeri pada kanker merupakan gejala yang sering dirasakan oleh pasien kanker. Penyebab nyeri antara lain penekanan sel kanker pada jaringan, terapi, dan infeksi. Nyeri dapat mengganggu aktivitas sehari-hari sehingga kualitas hidup pasien menurun. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara nyeri dan kemampuan aktivitas pada pasien kanker kolorektal. Desain penelitian yang digunakan yaitucross sectional. Subyek penelitian sebanyak 48 pasien kanker kolorektal dengan kemoterapi ditentukan dengan teknik simple random sampling. Data dikumpulkan dengan menggunakan Numeric rating Scale (NRS) dan KATZ Index. Analisis data yang digunakan yaitu uji pearson prooduct moment. Nilai rata-rata nyeri yaitu 4,58 SD 1,29. Nilai rata-rata kemampuan aktivitas yaitu 4,40 SD 1,20. Hubungan antara nyeri dan aktivitas didapatkan koefisien korelasi -0,581 dan p =0,000. Ada hubungan antara nyeri dan kemampuan aktivitas pada pasien kanker kolorektal yang menjalani kemoterapi. Perlu adanya peningkatanmanajemen nyeri pada pasien kanker sehingga aktivitas tidak terganggu. Kata kunci : nyeri, aktivitas, kanker kolorektal ABSTRACT Cancer pain is a common symptom experienced by cancer patients. The causes of cancer pain are suppresion of cancer tissue, therapy, and infection. Pain can interfere with activity daily living so patient quality of life decreases. Objective of this study wasto analyze association between pain and activity of colorectal cancer. A cross-sectional study was used in this study.Subject of the study consisted of 48colorectal patients with chemotherapy specified using simple random sampling technique. Data were obtained through numerik rating scale (NRS) for pain and KATZ index for activity. Data analysis used pearson prooduct moment. Mean of pain was 4,58 SD 1,29. Mean of activity was 4,40 SD 1,20. Association between pain and activity showed score of correlation coefficient -0,581 and p=0.000. There was association betweenbetween pain and activity of colorectal cancer. There is a need to improve cancer pain management so activity is not disrupted. Keywords : pain, activity, colorectal cancer DAFTAR PUSTAKA WHO. Latest world cancer statistics [Internet]. (2012) [cited 2016 May 15]. Available from: www.iarc.fr/en/mediacentre/pr/2013/pdfs/pr223_E.pdf Keslen D. (2008). Principles and Practice of Gastrointestinal Oncology.. second edition. philadelphia: Lippincott William and Wilkins. Herdman T. (2015). Nursing Diagnoses : Definition and Classification 2015-2017. Oxford: Wiley-Blackwell O’Connor M, Weir J, Butcher I et al. (2012). Pain in patients attending a specialist cancer service: prevalence and association with emotional distress. J Pain Symptom Manag. 43(29-38). Van den Beuken-van Everdingen MH, de Rijke JM, Kessels AG et al. (2007). Prevalence of pain in patients with cancer: a systematic review of the past 40 years. Ann Oncol. Vol:18 hal: 1437–49. Mercadante S. (2007). Why are our patients still suffering pain? Nat Clin Pr Oncol.Volume: 4 hal :138–9. Beck DE, Roberts, Patricia L. Saclarides, Theodore J. Senagore, Anthony J. Stamos MJ , Wexner SD. (2011). The ASCRS Textbook of Colon and Rectal Surgery. second edi. New York: Spinger Lowery AE, Starr T, Dhingra LK, Rogak L, Hamrick-price JR, Farberov M, et al. (2011). Frequency , Characteristics , and Correlates of Pain in a Pilot Study of Colorectal Cancer Survivors 1 – 10 Years Post-Treatment. journal Pain Med. vol 14:1673–80. Ovayolu Ö, Ovayolu N, Aytaç S. (2014). Pain in cancer patients : pain assessment by patients and family caregivers and problems experienced by caregivers. Support Care Cancer. Beck SL, Dudley WN BA. (2005). Pain, sleep disturbance, and fatigue in patients with cancer: using a mediation model to test a symptom cluster. journal Oncology Nursing Forum. vol 32:542. Widyaningsih S. (2013). Thesis. A Survey of Symptom Experience, Symptom Management and Quality of Life of Indonesian Patient With Advance Cancer. Prince of Songkla University. Te Boveldt N, Vernooij-Dassen M, Burger N, Ijsseldijk M, Vissers K, Engels Y. (2013). Pain and its interference with daily activities in medical oncology. Pain Physician. Vol 16 No 4:379–89. Oosterling A, te Boveldt N, Verhagen C, van der Graaf W, Van Ham M, Van der Drift M, et al. (2015). Neuropathic Pain Components in Patients with Cancer: Prevalence, Treatment, and Interference with Daily Activities. Off J World Inst Pain. vol 16 No4:413–21. Wagner LI, Cella D. (2004). Fatigue and cancer: causes, prevalence and treatment approaches. Br J Cancer [Internet]. vol 91 no 5 :822–8. Available from: http://apps.webofknowledge.com.ezproxy.brighton.ac.uk/full_record.do?product=UA&search_mode=General Search&qid=16&SID=T2SsuknT6WsUluUeGJO&page=2&doc=16&cacheurlFromRightClick=no Albrecht TA, Taylor AG. (2010). Physical Activity in Patients With Advanced-Stage Cancer: A Systematic Review of the Literature. Clin J Oncol Nurs. Vol 16 No 3. DOWNLOAD FULL TEXT PDF >>